ArgR of Streptomyces coelicolor Is a Pleiotropic Transcriptional Regulator: Effect on the Transcriptome, Antibiotic Production, and Differentiation in Liquid Cultures - Botas, Alma; Pérez-Redondo, Rosario; Rodríguez-García, Antonio; Álvarez-Álvarez, Rubén; Yagüe, Paula; Manteca, Angel; Liras, Paloma (Frontiers in Microbiology, 2018)
ArgR is a well-characterized transcriptional repressor controlling the expression of arginine and pyrimidine biosynthetic genes in bacteria. In this work, the biological role of Streptomyces coelicolor ArgR was analysed by comparing the transcriptomes of S. coelicolor ∆argR and its parental strain, S. coelicolor M145, at five different times over a 66-hour period. The effect of S. coelicolor ArgR was more widespread than that of the orthologous protein of Escherichia coli, affecting the expression of 1544 genes along the microarray time series. This S. coelicolor regulator repressed the expression of arginine and pyrimidine biosynthetic genes, but it also modulated the expression of genes not previously described to be regulated by ArgR: genes involved in nitrogen metabolism and nitrate utilization; the act, red and cpk genes for antibiotic production; genes for the synthesis of the osmotic stress protector ectoine; genes related to hydrophobic cover formation and sporulation (chaplins, rodlins, ramR and whi genes); all the cwg genes encoding proteins for glycan cell wall biosynthesis; and genes involved in gas vesicle formation. Many of these genes contain ARG boxes for ArgR binding. ArgR binding to seven new ARG boxes, located upstream or near the ectA-ectB, afsS, afsR, glnR and redH genes, was tested by DNA band-shift assays. These data and those of previously assayed fragments permitted the construction of an improved model of the ArgR binding site. Interestingly, the overexpression of sporulation genes observed in the ∆argR mutant in our culture conditions correlated with a sporulation-like process, an uncommon phenotype.